Brown adipose tissue - Pfeifer, Alexander; Klingenspor, Martin; Herzig, Stephan (Handbook of experimental pharmacology, 2019)
Part 1. Origin of Brown and Beige Adipocytes -- 1. Brown Adipose Tissue Development and Metabolism -- 2. Lessons from Cre-Mice and Indicator Mice -- 3. Aging of Brown and Beige/Brite Adipose Tissue -- 4. Adipogenesis in Primary Cell Culture -- 5. In Vitro Models for Study of Brown Adipocyte Biology -- 6. Brown-Like Adipocyte Progenitors Derived from Human iPS Cells: A New Tool for Anti-obesity Drug Discovery and Cell-Based Therapy? -- 7. Brown Adipose Tissue in Human Infants -- Part 2. Molecular Mechanisms of BAT Function and Signaling -- 8. Evolution of UCP1 -- 9. The Mechanism FA-Dependent H+ Transport by UCP1 -- 10. Role of cAMP and cGMP Signaling in Brown Fat -- 11. Fatty Acid Metabolites as Novel Regulators of Non-shivering Thermogenesis -- 12. Regulatory Small and Long Noncoding RNAs in Brite/Brown Adipose Tissue -- 13. Brown Adipokines -- Part 3 Detection of BAT in vivo -- 14. Infrared Thermography -- 15. In Vivo Detection of Human Brown Adipose Tissue During Cold and Exercise by PET/CT -- 16. Techniques and Applications of Magnetic Resonance Imaging for Studying Brown Adipose Tissue Morphometry and Function -- 17. Multispectral Optoacoustic Tomography of Brown Adipose Tissue -- 18. BAT Exosomes: Metabolic Crosstalk with Other Organs and Biomarkers for BAT Activity -- Part 4. Recruitment and Activation of human BAT -- 19. Activation of Human Brown Adipose Tissue (BAT): Focus on Nutrition and Eating -- 20. Translational Aspects of Brown Fat Activation by Food-Derived Stimulants -- 21. Translational Pharmacology and Physiology of Brown Adipose Tissue in Human Disease and Treatment
Keywords: Fettgewebe